Approach to the use of edible insects by indigenous communities of the eastern Colombian amazon - Gasca Álvarez, Héctor Jaime (2021)
In the Colombian Amazon, insects are an abundant natural resource, and part of the use of this resource is the consumption of some edible species. Historically, indigenous peoples are entomophagic and have included insects and other arthropods in their diets. In this paper, the traditional use of edible insects in the communities of the eastern Amazon of Colombia is analyzed. During August 2020 to March 2021, opened and semi-structured interviews carried out with inhabitants of the municipality of Mitú (Vaupés) and 41 surrounding indigenous communities were applied, inquiring about the perception, use and commercialization of edible insects. According to its use value, Rhynchophorus palmarum (Coleoptera: Curculionidae), Syntermes spinosus (Blattodea: Termitidae), Atta laevigata (Hymenoptera: Formicidae), Lusura chera (Lepidoptera: Notodontidae), and Polybia liliacea (Hymenoptera: Vespidae), are the most representative species of edible insects in the region. For each species, its ecological calendar was established, and its collecting techniques and methods, traditional forms of preparation and consumption, and marketing activities were documented. The potential of the edible insect species documented is highlighted to promote sustainable use strategies, with the aim of improving the food security of the population and maintaining the traditional knowledge of these communities.